A influência da dança do ventre na promoção da saúde e da qualidade de vida: uma revisão sistemática - SOUZA, Andressa Silva dos Santos (2023)
Objective: To analyze the influence of the practice of belly dancing on the health and quality of life of its practitioners. Methods: Retrospective documentary approach in the form of systematic review, following the PRISMA protocol directives. The BIREME, COCHRANE, LILACS, PEDRO, PUBMED and SCIELO platforms were used in the period 2010-2022, researched through the descriptors "belly dance," "quality of life," "effect" and "health". Included are studies, performed in practitioners of belly dance, professionals and amateurs, both genres, without restriction of age and language. Excluding case studies, experience reports, incomplete articles or articles that did not analyze effects of the practice of belly dancing. Results: Included in this review 15 studies, all carried out with women, aged between 18 and 80 years. Only 1 article had professionals of belly dance as participants of the research and the rest were beginners. Highlighted or allied to other modalities, the dance tends to contribute to the promotion of the quality of life of people, possessing great property of nonpharmacological intervention as in patient, as in cancer. Conclusion: a positive way, the intervention with belly dancing can contribute to treatments in patients that reflect the biopsychosocial well-being, being possibility of non-pharmacological treatment.usual diet was characterized by a low weekly intake of fruits, vegetables, whole grains, legumes, unsaturated oils, fish, oilseeds, teas and spices. Conclusion: It is concluded that the active adult population participating in this study has inadequate knowledge about functional foods, which are not included in their usual diet.